2012
DOI: 10.1111/j.1600-0722.2012.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ effect of sodium fluoride or titanium tetrafluoride varnish and solution on carious demineralization of enamel

Abstract: This study evaluated the effect of titanium tetrafluoride (TiF(4)) formulations on enamel carious demineralization in situ. Thirteen subjects took part in this cross-over, split-mouth, double-blind study performed in three phases of 14 d each. In each subject, two sound and two predemineralized specimens of bovine enamel were worn intra-orally and plaque accumulation was allowed. One sound and one predemineralized specimen in each subject was treated once with sodium fluoride (NaF) varnish or solution (Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 37 publications
10
51
1
4
Order By: Relevance
“…The main difference in the protocol of the present study is the no renew of the solutions during the cycling as pilot tests performed before this study demonstrated that there were no differences in the enamel lesions features obtained with or without these changes. The %SHL after the DE-RE cycling was greater than 90% and the values were similar to the obtained in a previous study [15], which also used this pH cycling model. Furthermore, the validation trough TMR performed in the present study also attested the creation of subsurface lesions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The main difference in the protocol of the present study is the no renew of the solutions during the cycling as pilot tests performed before this study demonstrated that there were no differences in the enamel lesions features obtained with or without these changes. The %SHL after the DE-RE cycling was greater than 90% and the values were similar to the obtained in a previous study [15], which also used this pH cycling model. Furthermore, the validation trough TMR performed in the present study also attested the creation of subsurface lesions.…”
Section: Discussionsupporting
confidence: 88%
“…In attempt to increase the fluoride retention, different strategies were described in previous studies [14,15,17,18]. Among these strategies, the use of phosphoric acid [17] and aluminum [16,18] was associated in this study as a pre-treatment of the enamel, aiming enhance the fluoride potential of remineralization based on these two interesting methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among those techniques are the 'gold standard' transverse microradiography (TMR), Knoop and Vickers microhardness either used perpendicular (K-SMH, V-SMH) or parallel to the hard tissue surface, polarized light and confocal laser scanning microscopy (both used parallel to the surface), and quantitative light-induced fluorescence (used perpendicular to the surface). Researchers have either shown good [4,21,22] or poor correlations [23,24] between TMR and SMH, depending on the extent of demineralization and lesion mineral distribution. However, previous 5 laboratories approximately monthly; however, determinations of origin, exact age and other characteristics of the donor (human or animal) are impossible due to the large number of teeth received.…”
Section: Introductionmentioning
confidence: 99%